Evaluating the therapeutic potential of BSA-reduced mussel-derived selenium nanoparticles to mitigate copper sulfate-induced hepatic damage and neurodegeneration in a zebrafish model - Umapathy, Suganiya; Pan, Ieshita (Frontiers in Genetics, 2025)
IntroductionLiver fibrosis is the abnormal accumulation of extracellular matrix and eventual formation of fibrous scar in response to chronic liver injury, which can be triggered by increased levels of reactive oxygen species. The brain-liver axis is a crucial communication pathway that significantly influences the intricate interactions between hepatic function and brain health. Selenium, as a source of selenoproteins, plays a vital role in antioxidant defense systems. The extraction of selenium from mussels leverages their natural bioaccumulation, providing a biocompatible source. Selenium nanoparticles are known for their potential antioxidant activity and can be employed to regulate ROS levels to overcome hepatic damage.MethodsSelenium nanoparticles were synthesized from mussel-extracted selenium and stabilized with bovine serum albumin. The zebrafish models exposed to copper sulfate were treated with selenium nanoparticles (5-25 μg/ml). This study evaluated their potential role as antioxidants against hepatic damage induced by copper sulfate in vivo in the zebrafish model.ResultsThe bovine serum albumin stabilized selenium nanoparticles reduced for 30 minutes and 1 hour were spherical with a size of 19 and 16 nm. Stabilized selenium nanoparticles reduced for 30 minutes (25 μg/ml) showed significant in vitro reactive oxygen species scavenging activity and improved in vivo antioxidant enzyme levels by decreasing lipid peroxidation and nitric oxide levels. Histopathological examination revealed a delay in the progression of copper sulfate-induced hepatic damage, and upregulated the expression of antioxidants, while the hepatic and mitochondrial damage markers were downregulated.ConclusionIn conclusion, bovine serum albumin-reduced selenium nanoparticles can be a promising therapeutic antioxidant for protecting against reactive oxygen species-induced hepatic damage and neurodegeneration.